TP53 expression in PCAT in coronary artery disease combined with type 2 diabetes mellitus and its correlation with CCTA radiomic features: novel imaging biomarkers - Qi, Haicheng; Hu, Yahui; Li, Yan; Li, Xiumei; Xing, Yan (Frontiers in Medicine, 2025)
AimsTo explore the changes in differentially expressed genes in pericoronary adipose tissue (PCAT) and serum from patients with coronary artery disease (CAD) complicated with type 2 diabetes mellitus (T2DM) and to analyse its correlation with PCAT radiomic features based on coronary CT angiography (CCTA).MethodsIntersecting genes that were differentially expressed in both CAD and T2DM patients were obtained from the GEO database and analyzed to obtain candidate genes. PCAT and serum samples were collected from CAD patients who underwent coronary artery bypass grafting (CABG) from May 2023 to January 2024. RT–qPCR was used to determine the expression of candidate differentially expressed genes in PCAT, to search for genes related to patients with CAD combined with T2DM, and to verify the protein expression levels by immunohistochemistry (IHC). Enzyme-linked immunosorbent assays (ELISAs) were also used to determine the expression of candidate differentially expressed genes in the serum. Finally, the PCAT radiomic features of the right coronary artery in patients with CAD combined with T2DM were extracted and correlated with the candidate genes.ResultsHLA-DRB1, TP53, and CCR9 were screened from the GEO database. RT–qPCR results revealed that TP53 expression was significantly increased in the T2DM group compared with the control group (3.082 ± 0.580 vs. 1.663 ± 0.698, p < 0.001). IHC results revealed that the area of positive expression around the nucleus was increased in the fat cells of the T2DM group compared with those of the control group, with increased perinuclear areas with positive expression (0.521 ± 0.082 vs. 0.327 ± 0.074, p < 0.001), and 14 PCAT radiomic features in CAD combined with T2DM patients correlated with TP53 (rs > 0.5, p < 0.05).ConclusionTP53 expression was significantly elevated in the PCAT of patients with CAD combined with T2DM, suggesting that this molecule plays a role in the development of this disease. Four first-order features and 10 texture features in the PCAT radiomic features were associated with abnormal TP53 expression. The association of radiomic features with TP53 suggests that CCTA-based radiomic features can be used to predict abnormalities in differential gene expression, thus providing a new way to noninvasively predict CAD combined with T2DM.